PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK LANTAI KAYU DAN PINTU PT.PIJI DI JAWA TIMUR - Permana, Dony Indra (Jurnal Performa: Jurnal Manajemen dan Start-up Bisnis, 2017)
The purpose of this research is to find out whether the promotion product purchase decisions affect the wood floors and doors, PT. PIJI in East Java. The population in this research is the consumer PT. PIJI who purchase and use products wood floor or door in East Java. Determination of a sample using simple random sampling where to be sampled in this study must meet several conditions set by the researchers. The samples on this research totalled 50 respondents by using numerical formulas. Data collection is carried out using a questionnaire that has been determined by the researchers. The variables contained in the research is composed of free variables: age, occupation, and earnings while the variable is bound in this research is the purchasing decision. Analysis tools used are doing test t, then the determination of the coefficient of regression analysis simple and ends with a classic assumption test. The research results prove that there is a presence of the influence the promotion product purchase decisions against the wooden floor and doors PT. PIJI in East Java where the variable promotion effect of dominant 5, 88 and based on the results of a simple linear regression analysis showed that the promotion of a positive impact towards the enhancement of the purchasing decision. Views of the significance of the value of the variable t in the promotion test of 6, 636, therefore it can be concluded that the variable promotion has significant influence consumer buying decision variables against PT. PIJI.